Perilaku Tanah Longsoran di Jalan Sultan Sulaiman Kecamatan Sambutan, Samarinda Kalimantan Timur - Oktaviani, Revia; Benny Christian BB; Windhu Nugroho; Tommy Trides; Albertus J Pontus (Retii, 2023)
Clayey silt is one of the soils that cause many problems in infrastructure. The nature of clay depends on the dominance of the minerals it contains, this can give different behavior between clayey silt in one place and clayey silt in another place. This study aims to determine the behavior of clayey silt material in landslides on Sultan Sulaiman Road, Sambutan sub-district of Samarinda and find relationships between its physical properties including plasticity index relationship with water content and swelling. USCS classification results are included in the silt (ML) group. From the test results of moisture content ranged from 26.3% - 36.3%, Atterberg boundary tested resulted in a soil plasticity index of 28.7%, 17.3%, 14.7%, 14.7%, 13.8%, 2.6% and has an average of 15.3%. The average development percentage obtained is 1.7%, so the expansive degree of development potential is still in the low category, while the resulted of the landslide development pressure test are 135 kPa, 130 kPa, 66 kPa, 64 kPa, 39 kPa, 35 kPa with an average result of 78.2 kPa, also included in the low development potential group.